In Situ Synthesis and Applications for Polyinterhalides Based on BrCl. Issue 66 (22nd October 2020) - Schmidt, Benjamin; Ponath, Sebastian; Hannemann, Johannes; Voßnacker, Patrick; Sonnenberg, Karsten; Christmann, Mathias; Riedel, Sebastian
Abstract: The use of neat BrCl in organic and inorganic chemistry is limited due to its gaseous aggregate state and especially its decomposition into Cl2 and Br2 . The stabilization of BrCl in form of reactive ionic liquids via a novel in situ synthesis route shifts this equilibrium drastically to the BrCl side, which leads to safer and easier‐to‐handle interhalogenation reagents. Furthermore, the crystalline derivatives of the hitherto unknown [Cl(BrCl)2 ] − and [Cl(BrCl)4 ] − anions were synthesized and characterized by single‐crystal X‐ray diffraction (XRD), Raman and IR spectroscopy, as well as quantum chemical calculations. Abstract : A new synthesis route enables the stabilization of the toxic gas BrCl in form of reactive ionic liquids (ILs). With these ILs it is possible to interhalogenate Michael systems, alkenes and alkynes in fast reaction times. Furthermore a complete set of the possible BrCl interhalides with one to six coordinating BrCl molecules was synthesized, including the hitherto unknown [Cl(BrCl)2 ] − and [Cl(BrCl)4 ] − anions.